Perananan Bimbingan Agama Dalam Mencegah Perjudian Online pada Kalangan Remaja di Desa Kuta Ujung Kecamatan Darul Hasanah Kabupaten Aceh Tenggara - Alfi Sahri; Winda Kustiawan (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
The rapid development of technology has made it the foundation of all human life. This can be seen in the pattern of human life that cannot be separated from technology. Technology has very positive benefits and can make human work easier if used properly and correctly, but technology can also have a vicious effect if it is not used wisely. One of the negative impacts produced by technological developments is that it is easy for teenagers to access online gambling. Gambling has been banned in religion, culture and criminal law. Teenagers who are expected to be the next generation of the nation will experience damaged morale if they continue to play online gambling. The impact of gambling is also very bad for teenagers. Qualitative research is the type of research used in this study, the chosen location is Kuta Ujung Village, Darul Hasanah District, Southeast Aceh District. Interviews, observation and documentation are data collection techniques, and Miles and Huberman's opinions are data analysis techniques. Factors that cause online gambling range from weak faith, bad environment, low level of education, lack of time, curiosity, addiction and also difficult economic factors. The role of religious guidance is very, very important for teenagers to prevent online gambling. Guidance by giving religious lectures, forming mosque youth and creating recitation programs for youth are the efforts of village authorities in motivating, facilitating and consolidating to prevent the rise of online gambling by teenagers. Keywords: Online Gambling, Technological Developments, Adolescents